Analysis of Contamination of Lead Metal (Pb) and Cadmium (Cd) in Whitening Serum Circulating in Online Stores with Atomic Absorption Spectrophotometry - Iswandi Iswandi (AFAMEDIS, 2023)
Abstract Various cosmetic preparations are developing in line with technological developments in online marketing today, one of which is serum whitening. Whitening serum is a series of facial skin care products that contain certain active ingredients used for the health of facial skin with the aim of whitening the face. Online sales of cosmetics have a bad impact, namely the spread of cosmetics that have not been registered with BPOM, so it is feared that contamination from contamination materials such as heavy metals lead (Pb) and cadmium (Cd). So there is a need for a qualitative and quantitative analysis with atomic absorption spectrophotometry and method verification. This study aims to identify the presence of lead (Pb) and cadmium (Cd) metal contamination in whitening serums so as to advise consumers about the dangers of using these metals for facial skin health. The results showed that the 5 samples analyzed all contained lead metal contamination (Pb) in the range of 0.0191-0.0406 mg / L and cadmium metal (Cd) in the range of 0.7732-0.9871 mg / L. Results still met the requirements in accordance with the BPOM contamination limit, namely no more than 20 mg / L and no more than 5 mg / L. Thus, all the serum whitening sample is still within the safe limit according to the contamination limit by BPOM.